The Apartment Building and the Index of Despair - Zografakis, Stavros (Études helléniques / Hellenic Studies, 2014)
The deterioration in social indicators in Greece as a result of the crisis, which is now in its sixth year, has been confirmed with a considerable lag. The dramatic increase in unemployment and the pressure on workers to accept wage cuts in exchange for keeping their jobs have been driving more and more households to despair. The aim of the study is to measure the despair of Greek households, using an index constructed on the basis of raw data from ELSTAT’s Labour Force Survey. The index provides a timely measure, at a quarterly frequency, of the despair of households and examines how the burden of a fiscal adjustment achieved through wage cuts or job losses can be considered to be distributed “fairly” across households.